2011
DOI: 10.1007/s00439-011-0981-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel prostate cancer susceptibility variant in the KLK3 gene transcript

Abstract: Genome-wide association studies (GWAS) have identified more than 30 prostate cancer (PrCa) susceptibility loci. One of these (rs2735839) is located close to a plausible candidate susceptibility gene, KLK3, which encodes prostate-specific antigen (PSA). PSA is widely used as a biomarker for PrCa detection and disease monitoring. To refine the association between PrCa and variants in this region, we used genotyping data from a two-stage GWAS using samples from the UK and Australia, and the Cancer Genetic Markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 20 publications
6
67
0
Order By: Relevance
“…6,[8][9][10][11][12][13][14][15][16] For some cancers, these splicing alterations create functionally significant biomarkers. 9,12,14,[17][18][19][20][21] In light of these studies and the results presented here, we believe that NOTCH2 and FLT3 splicing events are associated with pathogenesis in AML and that identification of the causes and consequences of these splicing alterations will provide a better understanding of the biology of this disease. Because it is well known that splicing alterations can result from mutations and/or could be due to modulated expression of splicing factors, we evaluated whether expression of NOTCH2 and FLT3 splice variants correlated with mutations detected on commonly mutated genes such as U2AF1 and SF3B1 in patients with AML (supplemental Figure 4).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…6,[8][9][10][11][12][13][14][15][16] For some cancers, these splicing alterations create functionally significant biomarkers. 9,12,14,[17][18][19][20][21] In light of these studies and the results presented here, we believe that NOTCH2 and FLT3 splicing events are associated with pathogenesis in AML and that identification of the causes and consequences of these splicing alterations will provide a better understanding of the biology of this disease. Because it is well known that splicing alterations can result from mutations and/or could be due to modulated expression of splicing factors, we evaluated whether expression of NOTCH2 and FLT3 splice variants correlated with mutations detected on commonly mutated genes such as U2AF1 and SF3B1 in patients with AML (supplemental Figure 4).…”
Section: Discussionsupporting
confidence: 52%
“…6,[8][9][10][11][12][13][14][15][16] For some cancers, these splicing alterations create functionally significant biomarkers. 9,12,14,[17][18][19][20][21] Using exome sequencing, frequent mutations in genes involved in regulating splicing were identified in myelodysplasia (MDS) and in some AML patients. 22 Recently, using a single nucleotide polymorphism (SNP) array and targeted sequencing of 1000 genes, novel somatic mutations of splicing factor SFPQ and splicing regulator CTCF were identified in 10% of AML patients.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the reporter assay result, indicating that this SNP is negatively modulating androgen regulation of MLPH expression. Previous GWAS studies have identified 2 prostate cancer susceptibility loci at 2q37.3 with the 2 SNPs rs2292884:A>G and rs7584330:A>G located either within or next to the MLPH gene (Haiman, et al, 2011; Kote-Jarai, et al, 2011a; Kote-Jarai, et al, 2011b; Schumacher, et al, 2011). The risk G allele of rs2292884:A>G, which has a stronger linkage disequilibrium with rs11891426:T>G compared to rs7584330:A>G, also strongly correlated with reduced MLPH gene expression in human prostates.…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper by Kote -Jarai et al (2011a) undertook an imputation approach to refine the association between SNPs in the KLK3 GWAS-identified region and prostate cancer. Using genotyping data from a two-stage GWAS using British and Australian samples (Eeles et al , 2009 ) and the Cancer Genetic Markers of Susceptibility study ( http://www.cgems.cancer.gov/ ), genotypes were imputed for 197 and 312 SNPs from HapMap Phase II and the 1000 Genomes project, respectively.…”
Section: Imputation: a New Tool For Fine-mapping Studiesmentioning
confidence: 99%